2016
DOI: 10.1021/acs.langmuir.6b00700
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corona Structure on Binding of an Ionic Surfactant in Oppositely Charged Amphiphilic Polyelectrolyte Micelles

Abstract: Interaction of polystyrene-block-poly(methacrylic acid) micelles (PS-PMAA) with cationic surfactant N-dodecylpyridinium chloride (DPCl) in alkaline aqueous solutions was studied by static and dynamic light scattering, SAXS, cryogenic transmission electron microscopy (cryo-TEM), isothermal titration calorimetry (ITC), and time-resolved fluorescence spectroscopy. ITC and fluorescence measurements show that there are two distinct regimes of surfactant binding in the micellar corona (depending on the DPCl content)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Additional information about the binding and localization of surfactant headgroups in mPNIPAm micelles was obtained by fluorescence quenching measurements with N -dodecanoyl­aminofluorescein (DAF) which strongly binds to nonpolar cores of various self-assembled associates with its fluorescent headgroup located in the innermost part of the water-soluble shell (close to the core–shell interface) . The fluorescence of DAF is quenched by DPCl headgroup and therefore the decrease of fluorescence emission and shortening of fluorescence lifetime reports on the close approach of DPCl headgroup to DAF headgroup. We followed the binding of DP + ions to mPNIPAm micelles and their localization by measuring the time-resolved fluorescence emission of DAF and by interpreting the results on the basis of the micellar quenching model .…”
Section: Resultsmentioning
confidence: 99%
“…Additional information about the binding and localization of surfactant headgroups in mPNIPAm micelles was obtained by fluorescence quenching measurements with N -dodecanoyl­aminofluorescein (DAF) which strongly binds to nonpolar cores of various self-assembled associates with its fluorescent headgroup located in the innermost part of the water-soluble shell (close to the core–shell interface) . The fluorescence of DAF is quenched by DPCl headgroup and therefore the decrease of fluorescence emission and shortening of fluorescence lifetime reports on the close approach of DPCl headgroup to DAF headgroup. We followed the binding of DP + ions to mPNIPAm micelles and their localization by measuring the time-resolved fluorescence emission of DAF and by interpreting the results on the basis of the micellar quenching model .…”
Section: Resultsmentioning
confidence: 99%
“…Instead, only single surfactant ions enter the corona, and surfactant micelles form in the corona periphery after saturation of the core/corona interface of the block copolymer micelle with the surfactant. 9 PE−S aqueous solutions at or close to the stoichiometric charge ratio often undergo phase separation of the solid waterinsoluble PE−S complex. 5,10 Double-hydrophilic block copolymers, consisting of a polyelectrolyte block and a neutral hydrophilic block, mixed with the oppositely charged surfactant at the stoichiometric charge ratio yield core−shell nanoparticles (spherical or cylindrical micelles, vesicles) resembling those of amphiphilic diblock copolymers, with the core of the PE−S complex and with the corona of the neutral hydrophilic block.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When the surfactant binds to a dense polyelectrolyte brush, as in the case of amphiphilic block copolymer micelles with polyelectrolyte coronas, cooperative binding does not occur because surfactant micelles cannot be accommodated in the brush for sterical reasons. Instead, only single surfactant ions enter the corona, and surfactant micelles form in the corona periphery after saturation of the core/corona interface of the block copolymer micelle with the surfactant …”
Section: Introductionmentioning
confidence: 99%
“…For example, we did not succeed in preparing onion micelles based on parent micelles with kinetically frozen cores (polystyrene cores, unpublished data). Further, we observed that, in systems with dense shells, even the penetration of C12 surfactants is problematic and highly restricted . In the former case, rigid cores restrict the mobility of the shell-forming PE chains, which hinders the penetration of oppositely charged PE chains toward the core.…”
Section: Resultsmentioning
confidence: 92%
“…Further, we observed that, in systems with dense shells, even the penetration of C12 surfactants is problematic and highly restricted. 71 In the former case, rigid cores restrict the mobility of the shell-forming PE chains, which hinders the penetration of oppositely charged PE chains toward the core. In the latter case, the strong steric constraints in the inner shell prevent the formation of surfactant micelles, and we found that, in contrast to common PE−surfactant systems, single surfactant molecules interact with PE chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%